Governance, Risk and Compliance in a Cutting-edge Perspective: Empirical Synthesis, Theoretical Gaps and Research Agendas - Ridwan; Muh. Risnandar; Muryani Arsal (LP2M IAIN Palopo, 2025)
This study aims to comprehensively examine the development of Governance, Risk, and Compliance (GRC) studies during the period 2013–2025 and identify inconsistencies in empirical findings, methodological fragmentation, and future research opportunities in the context of modern governance. Using a Systematic Literature Review (SLR) approach and thematic analysis, the study examined dozens of reputable articles from various international databases, including Scopus, ScienceDirect, Emerald Insight, Taylor & Francis, and Google Scholar. Literature selection was carried out through the PRISMA procedure, followed by the process of open coding, thematic synthesis, and mapping of the evolution trends of GRC research. The results show that the GRC literature is still fragmented and has not produced consistent conclusions about the influence of GRC on company performance and value. Empirical evidence shows that the results vary due to differences in GRC measurement instruments, unequal industry contexts, and inequality in the maturity level of GRC implementation across different organizations. Another important finding suggests that the integration of Governance, Risk, and Compliance (GRC) is still very limited, although these themes are increasingly relevant in modern corporate governance. This research contributes to formulating seven main research gaps and offers a future research agenda, including the development of the GRC Maturity Index, the Digital GRC Capability Model, conceptual integration of GRC–ESG, as well as the need for qualitative and mixed-methods approaches to understand the dynamics of GRC implementation in a more contextual and in-depth manner. These findings make an important theoretical contribution to strengthening the conceptual foundations of GRC as well as practical contributions for organizations looking to improve governance capabilities in the digital and sustainability-oriented era.